A Study on Physical Properties of Okra Pod and Seed - Kushwaha, H L; Srivastava, A P; Singh, Harpal (Journal of Agricultural Engineering, 2007)
A few selected physical properties of okra pod and seed were determined for creation of some basic data for application in designing seed extractor. The average geometrical mean diameter, roundness and sphericity were found 4.9 mm, 79.3% and 86.4%, respectively at the 11.2% moisture content (d.b.). The bulk density of seed was found 0.58 g/cc whereas, true density, porosity and volume were 1.2 g/cc, 49.1% and 0.7 cc, respectively. The mean value of angle of repose and coefficient of static friction of seed were 28.7degree and 0.21, respectively. The terminal velocity of okra seed increased from 3.3 to 3.6 m/s as the moisture content increased from 10.8 to 15.5 % (d.b.). The compressive strength of the pod varied from 146.1 to 238.3 N at the corresponding displacement of 5.8 to 7.0 mm and for the pod head from 121.6 to 169.5 N, at the corresponding displacement of 4.1 to 5.8 mm. The mean value of peak compressive force for seed to fail was 96.9 N at the corresponding displacement of 0.9 mm.